2015
DOI: 10.1002/bbb.1560
|View full text |Cite
|
Sign up to set email alerts
|

Microbial lipid production by cold‐adapted oleaginous yeast Yarrowia lipolytica B9 in non‐sterile whey medium

Abstract: Deproteinized whey was used as a substrate for the production of lipids by cold‐adapted yeast Yarrowia lipolytica B9 under non‐sterile culture conditions. Undesired microbial contamination in non‐sterile whey medium could be prevented when appropriate culture parameters (inoculum size of 3 mL/100 mL, initial pH of 5.5 and incubation temperature of 15 °C) were selected. In contrast to additional nitrogen (ammonium sulfate) and phosphorus (potassium dihydrogen phosphate) sources, additional carbon source (lactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 50 publications
3
28
1
Order By: Relevance
“…The same finding was observed by Huang et al (2012). Another study by Taskin et al (2015) showed that the highest content of lipid and biomass of oleaginous yeast Yarrowia lipolytica B9 were (28%) and (4.38 gl -1 ) with an inoculum size of 3 %. Jiru et al (2017) reported that 10% v/v inoculum size was the optimum inoculum size for lipid accumulation by Rhodotorula kratochvilovae.…”
Section: Effect Of Inoculum Sizesupporting
confidence: 81%
See 1 more Smart Citation
“…The same finding was observed by Huang et al (2012). Another study by Taskin et al (2015) showed that the highest content of lipid and biomass of oleaginous yeast Yarrowia lipolytica B9 were (28%) and (4.38 gl -1 ) with an inoculum size of 3 %. Jiru et al (2017) reported that 10% v/v inoculum size was the optimum inoculum size for lipid accumulation by Rhodotorula kratochvilovae.…”
Section: Effect Of Inoculum Sizesupporting
confidence: 81%
“…Similar feature was documented by Huang et al (2012) for oleaginous yeast; Trichosporon fermentans. Contrary, 15°C was favorable for oleaginous yeast Yarrowia lipolytica B9 (Taskin et al, 2015).…”
Section: Effect Of Temperaturementioning
confidence: 93%
“…That is to say the remaining sugar in the medium after the depletion of nitrogen source might be utilized for lipid synthesis. Because, investigators have reported that excessive carbon remains unutilized or is converted into storage polysaccharides in non-oleaginous species, while, it is preferentially channeled toward lipid synthesis in oleaginous species [14,25,32,34]. At the end of 132-hours cultivation period, the maximum lipid concentration and lipid content were determined as 7.82 g/L and 62 %, respectively.…”
Section: Optimization Of Culture Parameters For Lipid Production In Lmentioning
confidence: 99%
“…At the end of 48-cultivation period, absorbance of yeast starter cultures was adjusted to 2.0 (at 600 nm) using sterile saline-water [25,26]. Then, 2 mL of yeast seed culture were used for inoculation of LKEB medium.…”
Section: Preparation Of Yeast Seed Culturementioning
confidence: 99%
“…This is important to achieve higher bioproduct yields and productivity and, therefore, can improve the overall economics of industrial microbial processes. An industrially relevant host organism is the oleaginous yeast-Yarrowia lipolytica-which has gained a lot of attention recently for the production of lipids using various pure substrate (e.g., glucose, fructose, lactose, sucrose, glycerol, and xylose) and raw feedstocks (e.g., olive oil mill waste, whey, waste cooking oil, and animal fats) [26,32]. Oleaginous yeasts have a distinctive ability to convert certain organic acids directly to acetyl-CoA-the central intermediate of lipid biosynthesis-by acetyl coenzyme A synthetase.…”
Section: Introductionmentioning
confidence: 99%